2010
DOI: 10.1029/2009jd012016
|View full text |Cite
|
Sign up to set email alerts
|

What occurs in K process of cloud flashes?

Abstract: [1] The Lightning Research Group of Osaka University has been developing and improving the VHF broadband digital interferometer, which locates the impulsive VHF radiation sources caused by lightning discharges with extremely high time resolution in three dimensions. As a result of the VHF observations during the 2006-2007 monsoon season in Darwin, Australia, cloud flashes accompanied by K processes are clearly visualized in three dimensions with high time resolution. In the late stage of the cloud flashes, neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
33
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 19 publications
12
33
0
Order By: Relevance
“…Lightning sources of these impulsive emissions can be located via measurements at multiple ground‐based receivers using the “time‐of‐arrival” technique [ Proctor , ], such as the Lightning Mapping Array (LMA) developed by New Mexico Tech [ Rison et al ., 1999; Thomas et al ., ]. Positive leaders through negatively charged cloud regions are less impulsive, while their trails can be resolved by detecting associated retrograde negative breakdown (so‐called “recoil leaders” or K processes) when they encounter localized negative charge concentrations [ Thomas et al ., ; Akita et al ., ]. Therefore, the LMA‐resolved lightning structure provides an alternative way to construct the gross charge structure of thunderclouds in addition to balloon soundings of electric field profile [ Winn et al ., ; Stolzenburg et al ., ; Coleman et al ., ; Carey et al ., ; Rust et al ., ; Bruning et al ., ].…”
Section: Instrumentation Network and Methodsmentioning
confidence: 99%
“…Lightning sources of these impulsive emissions can be located via measurements at multiple ground‐based receivers using the “time‐of‐arrival” technique [ Proctor , ], such as the Lightning Mapping Array (LMA) developed by New Mexico Tech [ Rison et al ., 1999; Thomas et al ., ]. Positive leaders through negatively charged cloud regions are less impulsive, while their trails can be resolved by detecting associated retrograde negative breakdown (so‐called “recoil leaders” or K processes) when they encounter localized negative charge concentrations [ Thomas et al ., ; Akita et al ., ]. Therefore, the LMA‐resolved lightning structure provides an alternative way to construct the gross charge structure of thunderclouds in addition to balloon soundings of electric field profile [ Winn et al ., ; Stolzenburg et al ., ; Coleman et al ., ; Carey et al ., ; Rust et al ., ; Bruning et al ., ].…”
Section: Instrumentation Network and Methodsmentioning
confidence: 99%
“…After leaders stop propagating, there are repeated jumps of the electric field at the ground (and aloft), called K changes [ Ogawa and Brook , 1964], which are produced by propagating discharges similar to dart leaders in that they carry negative charge along a channel previously ionized by a negative leader in the same direction as the negative leader [ Ogawa and Brook , 1964; Shao et al , 1995; Mazur , 2002; Akita et al , 2010]. The discharges that produce K changes have been have given many names.…”
Section: Introductionmentioning
confidence: 99%
“…A summary of research on pulses and currents in lightning flashes can be found in the book by Rakov and Uman [2003, chapters 4 and 7]. For more recent results and reviews on triggered flashes and flashes to towers see the articles by Rakov et al [2003], Miki et al [2005], Campos et al [2007], Flache et al [2008], Campos et al [2009], Akita et al [2010], and Qie et al [2011].…”
Section: Introductionmentioning
confidence: 99%